Dendritic Cells - Chapoval, Svetlana P. (IntechOpen, 2018)
Since their discovery in 1973 by Zanvil Cohn and Ralph Steinman (Nobel Prize in Physiology and Medicine, 2011), dendritic cells (DCs) continue to intrigue research scientists as their new markers, subpopulations and properties are being detected and the relevant literature is being doubled each year. This book combines the most comprehensive reviews of several critical aspects of DC biology and function written by a group of international experts in the field. The first section briefly discusses recent advances in DC subtypes, phenotypes, and functions in different diseases. The following sections look closely at DC phenotyping, DC-NK cell interplay, and roles of DC in bone loss and repair and parasitic infections. The final section on DC and cancer includes perspectives on DC vaccination based on modifications and therapeutic applications.